Spiritual Nexus: The Interwoven Sacred Sites of the Kailash Region - Lama, Nabraj (Global Journal of Cultural Studies, 2024)
This article investigates the complex network of sacred sites within the Kailash region, an axis of profound spiritual significance for a multitude of faiths. The central figure of this sacred web is Mount Kailash, surrounded by the mystical Lake Manasarovar and Rakshas Tal, the restorative springs of Tirthapuri, and the reflective sanctuary of the Bon Monastery. This study delves into the spiritual importance, historical connections, and intricate cultural practices maintained across these sites. Darchen, the starting point for the spiritually charged Kailash Kora, marks the pilgrims' journey towards potential enlightenment. Moreover, the paper investigates the ecocultural dynamics, emphasizing the monasteries around Manasarovar, including the Bon Monastery, as enduring custodians of spiritual wisdom despite historical tribulations. Harnessing a variety of interdisciplinary perspectives, the article portrays how these sites collectively constitute a spiritual heritage that continually shapes the socio-religious fabric of the region. It also addresses modern challenges due to increased pilgrimage, advocating for sustainable conservation efforts. By intertwining the cosmic symbolism and earthly presence of these sites, this article contributes a holistic view of the Kailash region's perpetual sacredness and its essential place within the global spiritual domain.